PENGARUH KUALITAS LAYANAN, PRODUCT, DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN PADA BIRO TOUR AND TRAVEL PT. U&I HOLIDAYS BALI - Ni Kadek Dwi Pratiwi; Anak Agung Putu Agung; Ni Putu Yeni Astiti (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The purpose of this study was to test and obtain empirical evidence of the effect of service quality, product, and brand image on customer loyalty. The population in this study are consumers who use tour travel services whose numbers are not known in detail even though the total sales are known at PT.U & I Holidays Bali. The sample in this study were 100 respondents who were determined based on the non-probability sampling method, namely accidental sampling. The data analysis technique used is multiple linear regression. The results showed that service quality, product, and brand image had a positive effect on customer loyalty. Discussions and limitations of teacher research are presented.